Dynamic characteristics of external luminance of highway tunnel in cold area. Issue 1 (October 2020) - Wang, Yansong; Zhao, Yuguo; Quan, Qunshan; Cao, Zhengmao
Abstract: The external luminance of highway tunnels in cold areas is a key parameter for the lighting design of the tunnel entrance section. Due to the influence of the tunnel portal form, tunnel orientation, solar radiation intensity and solar irradiation angle, the external luminance of the tunnel varies with different seasons and different times. At present, there are relatively few studies on the time-varying characteristics of the external luminance of highway tunnels in cold areas. Relying on the Wunvfeng extra-long tunnel, combined with different tunnel opening orientations, the changes in the luminance of the tunnel exterior with time under several typical weather conditions are analyzed. The dynamic characteristics of the external luminance outside the tunnel in the cold area was obtained, which provide more detailed and reliable data for tunnel design. It has reference value for the lighting design and operation control of the entrance section of the tunnel and the design of light reduction outside the tunnel.